Proof of life : twenty days on the hunt for a missing person in the Middle East - Levin, Daniel, 1963- (Algonquin Books of Chapel Hill, 2021)
"An account by an armed-conflict mediator searching for a missing person in Syria over twenty tense days-at the end of which he will either find "proof of life" or not"--